Direct angiotensin II type 2 receptor stimulation decreases dopamine synthesis in the rat striatum - Mertens, Birgit; Vanderheyden, Patrick; Michotte, Yvette; Sarre, Sophie (Neuropharmacology, 2010)
A relationship between the central renin angiotensin system and the dopaminergic system has been described in the striatum. However, the role of the angiotensin II type 2 (AT2) receptor in this interaction has not yet been established. The present study examined the outcome of direct AT2 receptor stimulation on dopamine (DA) release and synthesis by means of the recently developed nonpeptide AT2 receptor agonist, compound 21 (C21). The effects of AT2 receptor agonism on the release of DA and its major metabolite 3,4-dihydroxyphenylacetic acid (DOPAC) and on the activity of tyrosine hydroxylase (TH), the rate-limiting enzyme in the catecholamine biosynthesis, were investigated using in vivo microdialysis. Local administration of C21 (0.1 and 1 μM) resulted in a decrease of the extracellular DOPAC levels, whereas extracellular DA concentrations remained unaltered, suggesting a reduced synthesis of DA. This effect was mediated by the AT2 receptor since it could be blocked by the AT2 receptor antagonist PD123319 (1 μM). A similar effect was observed after local striatal (10 nM) as well as systemic (0.3 and 3 mg/kg i.p.) administration of the AT1 receptor antagonist, candesartan. TH activity as assessed by accumulation of extracellular levels of l-DOPA after inhibition of amino acid decarboxylase with NSD1015, was also reduced after local administration of C21 (0.1 and 1 μM) and candesartan (10 nM). Together, these data suggest that AT1 and AT2 receptors in the striatum exert an opposite effect on the modulation of DA synthesis rather than DA release.